2021
DOI: 10.3389/fmed.2021.626423
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Non-coding RNAs in Diabetic Nephropathy-Related Oxidative Stress

Abstract: Diabetic nephropathy (DN) is one of the main complications of diabetes and the main cause of diabetic end-stage renal disease, which is often fatal. DN is usually characterized by progressive renal interstitial fibrosis, which is closely related to the excessive accumulation of extracellular matrix and oxidative stress. Non-coding RNAs (ncRNAs) are RNA molecules expressed in eukaryotic cells that are not translated into proteins. They are widely involved in the regulation of biological processes, such as, chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 134 publications
0
8
0
Order By: Relevance
“…Long non-coding RNAs (lncRNAs) are key regulators in DN (6,7). For instance, Ge et al reported that lncRNA NR_038323 alleviated renal fibrosis via sponging miR-324-3p and inactivating p38MAPK and ERK1/2 pathways (8).…”
Section: Highlight Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are key regulators in DN (6,7). For instance, Ge et al reported that lncRNA NR_038323 alleviated renal fibrosis via sponging miR-324-3p and inactivating p38MAPK and ERK1/2 pathways (8).…”
Section: Highlight Introductionmentioning
confidence: 99%
“…Interestingly, many recent studies have investigated the antioxidant and anti-inflammatory effects of these inhibitors. 6 - 13 …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, many recent studies have investigated the antioxidant and antiinflammatory effects of these inhibitors. [6][7][8][9][10][11][12][13] Further, many antioxidants, anti-inflammatory, and antiinfective bioactive compounds have been studied to be effective biocontrols against animal and human diseases including zoonotic conditions of intestine. 3,[14][15][16][17][18] Nevertheless, antioxidants are mostly present in fruits and vegetable and possess great potential against oxidative damage.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] The pathological manifestations associated with DN include glomerular thylakoid cells hypertrophy and hyperplasia, extracellular matrix (ECM) accumulation, podocytes function impairment and renal fibrosis. 9,10 Some studies have been partially demonstrated that circRNAs can act as microRNA sponges to influence the pathogenesis of DN, for instance, An et al have shown that hsa_circ_0003928 can bind to miR-151-3p and moderate Annexin A2 (ANXA2) expression via the microRNAs sponge, thereby attenuating high glucose-induced apoptosis in podocytes and glomerular thylakoid cells. 11 circRNA_0080425 is able to target miR-24-3p to regulate fibroblast growth factor 11 (FGF11) expression levels, which led to fibrosis and promoted DN progression.…”
Section: Introductionmentioning
confidence: 99%